Investigation of arbitrary large spatial dimensions in anisotropic Bianchi Type-I cosmologies with variable gravitational and cosmological parameters. Issue 1 (August 2021) - Goetz, A.; Secrest, J.A.
Abstract : In order to highlight time-varying constants such as the universal gravitation constant and to elucidate the effects of higher dimensions on cosmological parameters in the universe, we developed a toy cosmological model based upon an anisotropic n -dimensional spatial universe within an ( n + 1)-dimensional spacetime. A dynamical power law model for dark energy is considered. The observational parameters of this cosmology are predicted and discussed. Considerable attention is devoted to the application of the extra-dimensional n -dimensional anisotropic cosmology model resulting in a universe consistent with current observations.